Política pública para mejorar la falta de recursos estatales como medio de control en los centros carcelarios y su debida rehabilitación. - Jaramillo Saritama., Johao Orlando (2023)
This research aims to highight the lack of Public Policies focused on improving the management of the General State Budget allocated to Correctional Facilities in order to meet the needs of the incarcerated individuals. The objective is to ensure their rights as individual by examining legal foundations, forming an opinion based on the research, and considering the reality of the Penitentiary system. The administration of the Public system must uphold International Treaties and Conventions, the Constitution, the Comprehensive Penal Code, and the Regulations of the National System of Social Rehabilitation, to name a few. Among the aforementioned rights that must be protected are the rights to health, education, work, access to water and food, recreation, and petitions of incarcerated individuals. The prominent factors identified in this research include a shortage of personnel, insufficient infrastructure for effective surveillance, the lack of successful social rehabilitation of incarcerated individuals, the lack of successful social rehabilitation of incarcerated individuals, the failure to comply with all aspects within Correctional Facilities, and the inadequate verification of the designated budget for Correctional Facilities. This research takes into account aspects such as sentencing, the purposes of sentencing, rehabilitation, personal, social, and opportunistic factors contributing to criminal offenses, reintegration into society, recidivism, the right to sentence execution, and the universal and fundamental rights of incarcerated individuals within Correctional Facilities.